Synthesis and characterization of 1H-1,2,4-triazole functional polymer electrolyte membranes (PEMs) based on PVDF and 4-(chloromethyl)styrene via photoinduced grafting - Sasa, Derya; Sinirlioglu, Deniz; Muftuoglu, Ali Ekrem; Eren, Fatime; Celik, Sevim Unugur; Bozkurt, Ayhan (SPRINGER, 2013)
This work exploits a novel photoinduced grafting methodology in the production of 1H-1,2,4-triazole functional anhydrous proton conducting poly(vinylidene flouride) (PVDF) membranes. High performance of PVDF and design feature of PCMS were combined in a graft copolymer, PVDF-g-PCMS, by the polymerization of 4-(chloromethyl)styrene on a PVDF base matrix under UV light. After having been functionalized with 1H-1,2,4-triazole, the polymers were doped with triflic acid (TA) at different stoichometric ratios with respect to triazole units and the anhydrous polymer electrolyte membranes were prepared. The composition and the structure of polymers were characterized by elemental analysis (EA), H-1-NMR and FTIR. Their thermal properties were examined by TGA and DSC. TGA demonstrated that the PVDF-g-PCMS and PVDF-g-PCMS-Tri(TA)(x) membranes were thermally stable up to 390 A degrees C and 300 A degrees C, respectively. DSC results illustrated the homogeneity of the materials. According to EA results, 79 % functionalization with 1H-1,2,4-triazole was achieved. Proton conductivity was measured by impedance spectroscopy. PVDF-g-PCMS-Tri(TA)(1) with a degree of grafting of 48 % showed a maximum proton conductivity of 0.02 Scm(-1) at 150 A degrees C and anhydrous conditions.
Keywords: PVDF; 4-(Chloromethyl)styrene; 1H-1,2,4-triazole; Graft copolymers; Photoinduced polymerization; Polymer electrolyte; PROTON-CONDUCTING MEMBRANES; FUEL-CELL MEMBRANES; ETFE FILMS; BLENDS; STYRENE; COPOLYMERIZATION; Polymer Science